Manajemen Konflik Bimbingan Konseling Kelompok pada Siswa di SMP Negeri 1 Parigi - Arip Ridwan Maulana; Aspi Nurjanah; Ratna Kurnia; Salsabila Azizatul Jannah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
The background to this research begins with the many interpersonal conflicts that occur in the school environment and the role of guidance and counseling teachers in handling interpersonal conflicts. The results of the preliminary study at SMPN 1 PARIGI show that there are interpersonal conflicts and they are handled by guidance and counseling teachers. The purpose of this research is to find out how conflict management is carried out in group counseling for students at SMP Negeri 1 Parigi. This type of research is descriptive research with a qualitative approach. The data collection techniques used were interviews and documentation. The subjects in this research were people who had direct contact with the implementation of guidance and counseling, namely school principals, guidance and counseling teachers, and homeroom teachers. After data analysis, the research results showed that the counseling services currently used by BK teachers at SMP Negeri 1 PARIGI in handling interpersonal disputes among students are information services, group guidance, data collection, calling parents, mediation and consultation services. service. The types of support services and activities used by guidance and counseling teachers are carried out in order to prevent and resolve interpersonal conflicts between students.